2021
DOI: 10.38016/jista.758312
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of WBANs MAC Protocols in Different dBm and OMNet++

Abstract: In present days, wireless sensor networks (WSN) have involved considerable attention of both academy and industry because of the varied range of contexts in which they could be used. The has wireless body area network (WBAN) become the most important standard for WSN, and several software and hardware platforms are built on it. The implementation and performance analysis of this standard is essential to understand the important limits of it. The simulation is one of the greatest valuable tools for protocol eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It has a very portable framework, hence it is compatible with different operating systems such as MAC , Linux, and Windows OS [23], [24], [25], [26]. The researchers in [27] examined five MAC layer protocols. They have created two scenarios using OMNET++ simulator with different numbers of nodes and power consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has a very portable framework, hence it is compatible with different operating systems such as MAC , Linux, and Windows OS [23], [24], [25], [26]. The researchers in [27] examined five MAC layer protocols. They have created two scenarios using OMNET++ simulator with different numbers of nodes and power consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, this study’s contribution is to simulate and implement data transmission on intelligent traffic lights utilizing the DSDV-AODV routing protocol on the VANET. Because of its simulation employing wireless network technology, the OMNET++ simulator employs the 802.11b wireless standard, which has long-term advantages and is now more frequently used than the 802.11a standard [ 11 , 12 , 13 ]. Some researchers have evaluated the performance of AODV, DSR, and DVR routing protocols, where the simulation results showed that AODV was more efficient, but DSR achieved the best results in terms of energy consumption [ 14 ].…”
Section: Introductionmentioning
confidence: 99%